Continuing professional development: perspectives of Kenyan nurses and midwives - Kemei, Janet; Etowa, Josephine (My University, 2021)
The purpose of this paper is to report the perceptions of continuous professional development by the nurses and midwives in a low resource country. These findings are part of a larger study on the experiences of nurses and midwives providing postpartum care in rural areas of Kenya. Besides being the main healthcare providers in rural areas, nurses in low resource countries have limited access to continuous professional development.
Keywords: nursing; midwifery; continuing professional development; low-middle income countries